2020
DOI: 10.3390/ijms21207596
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Transcriptome Analysis Reveals Candidate Transcripts Associated with the Process of Programmed B Chromosome Elimination in Aegilops speltoides

Abstract: Some eukaryotes exhibit dramatic genome size differences between cells of different organs, resulting from programmed elimination of chromosomes. Here, we present the first transcriptome analysis of programmed chromosome elimination using laser capture microdissection (LCM)-based isolation of the central meristematic region of Aegilops speltoides embryos where B chromosome (B) elimination occurs. The comparative RNA-seq analysis of meristematic cells of embryos with (Bplus) and without Bs (B0) allowed the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Alteration of Nuf2 in A. thaliana affects the microtubule organization and results in lagging chromatids (Li et al 2021). Interestingly, B-specific Nuf2 transcripts are also associated with the process of programmed elimination of B chromosomes in Aegilops speltoides embryos (Boudichevskaia et al 2020). Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of Nuf2 in A. thaliana affects the microtubule organization and results in lagging chromatids (Li et al 2021). Interestingly, B-specific Nuf2 transcripts are also associated with the process of programmed elimination of B chromosomes in Aegilops speltoides embryos (Boudichevskaia et al 2020). Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Many plants, like 15% of all eukaryotic species, carry, in addition to standard chromosomes (A chromosomes), the supernumerary B chromosomes (Hanlon et al, 2018). Although B chromosomes are expandable, and without any known function, they are preferentially inherited at the super-Mendelian frequency through the "chromosome drive" mechanism (Dalla Benetta et al, 2019;Ruban et al, 2020). Recent studies on rye species showed that the sister chromatids of B chromosomes do not separate (non-disjunct) during the asymmetrical division that produces the germ cells (sperm of the pollen) and somatic (vegetative) cell, and preferentially segregate on the asymmetrical spindle to the generative pole.…”
Section: Plants Wasps and B Chromosomesmentioning
confidence: 99%
“…This process, rerepeated through several generations, leads to the accumulation of supernumerary B chromosomes in the germ cells (Dalla Benetta et al, 2019). Ruban et al (2020) studied B chromosome behavior (elimination and drive) in developing roots and during the first mitosis of the pollen, respectively, in the goatgrass Ae.…”
Section: Plants Wasps and B Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent of centromere activity, B chromosomes demonstrate nondisjunction of chromatids and lagging in anaphase, resulting in micronucleation and subsequent elimination. This process might allow root tissues to survive the detrimental expression or overexpression of B chromosome-located root-specific genes with paralogs located on standard A chromosomes ( Boudichevskaia et al, 2020 ; Ruban et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%